The messiah of Shiraz : studies in early and middle Babism - MacEoin, Denis, 1949- (Iran Studies, 2009)
The 19th century saw an enormous shift in the authority structure of Iranian and Iraqi Twelver Shiʿism, with the victory of a theological school (Usulism) that stressed the power of the clergy. This is well known. What is less well known is that there was a parallel development of authority in the Shaykhi school and its offshoot, the Babi sect. Here, especially in later forms of Babism, the Shiʿite claim to charismatic authority reached its limits in hyperbolic attestations of divinity. The present text is in two parts: a study of how Shaykhism bifurcated into a form close to orthodoxy next to the highly unorthodox Babi movement. Part two examines how Babism changed after the death in 1850 of its founder, the Bāb.